Penerapan Keselamatan Dan Kesehatan Kerja (K3) Pada Proyek Perkuatan Badan Jalan Teluk Selong Kec. Martapura Barat, Kabupaten Banjar - Arifin; Misnawati; Ahmad Riduan; Widuri, Elva Shanty; Novianti, Trie Rezky; Setiady, Irsyandi Syifa; Chandra, Muhammad (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This community service activity was conducted in the Teluk Selong Road repair project, Martapura Barat District, Banjar Regency, with the main focus on improving the implementation of Occupational Health and Safety (OHS) through education on the use of Personal Protective Equipment (PPE) in piling works. The main issue faced was the high risk of work accidents due to the unstable environment along the Martapura River's edge and the use of heavy machinery during the construction process. This program aims to enhance workers' awareness and discipline regarding the importance of PPE usage and the implementation of safe work procedures according to OHS standards. The implementation methods included technical guidance, daily field supervision, and regular evaluations and feedback. The results of the activity showed a significant increase in PPE compliance among workers, the development of a better safety culture, and the creation of comprehensive documentation that can serve as a reference for similar projects in the future. This program not only had a direct impact on the protection of workers but also has the potential to encourage further research and the development of safety policies in the construction sector. Therefore, participatory OHS education has proven to be effective in improving work safety and productivity in high-risk project environments.